Effect of a digital family disaster plan e-book on earthquake preparedness among anesthesia nursing students - Ririn Zuhairini; Praditia Triwibowo; Ellyda Septiani Pramita; Gatot Suparmanto; Triyas Singgih Pambudi; Cahaya Nugraheni (Indonesian Nursing Journal, 2026)
Background: Indonesia, part of the Pacific Ring of Fire, experiences significant seismic activity. The Special Region of Yogyakarta is particularly susceptible to earthquake hazards, emphasizing the need to strengthen disaster preparedness awareness. A digital family disaster plan (FDP) was designed as an educational resource to guide families during earthquakes. Purpose: This study aims to examine the effect of the digital Family Disaster Plan (FDP) on the earthquake preparedness of second semester anesthesia students at Universitas 'Aisyiyah Yogyakarta (UNISA). Methods: This study employed a one-group pretest–posttest pre-experimental design and was analyzed using the Wilcoxon signed-rank test. The sample consisted of 64 second semester anesthesia students from Universitas 'Aisyiyah Yogyakarta, selected through random sampling. Data collection was conducted using a preparedness questionnaire. Results: Female respondents constituted the majority (59.4%). Baseline assessment showed 87.5% were unprepared prior to the intervention. After exposure to the digital FDP, 89.1% were classified as prepared. The Wilcoxon signed-rank test showed a statistically significant improvement in preparedness scores (p < 0.001), indicating the intervention was associated with improved disaster preparedness. Conclusion: The Digital Family Disaster Plan E-book intervention was associated with improved earthquake preparedness scores among second-semester anesthesia students at UNISA. However, this study was limited using a pre-experimental one-group design; therefore, future studies using randomized controlled trials are recommended to confirm the effectiveness of digital Family Disaster Plan interventions.